The story behind the first few cases of monkeypox infection in non-endemic countries, 2022 - Muna Abed Alah; Sami Abdeen; Elias Tayar; Iheb Bougmiza (Elsevier, 2022)
Starting May 6, 2022, a rising number of monkeypox cases started to be detected in different countries where the disease is not endemic. About 24 countries reported cases by May 28 mostly in Europe. Most of the reported cases so far were among young men particularly men who have sex with men or had a travel history to countries where cases are being registered. In this rapid review we summarized the story behind the first few cases of monkeypox virus infection in non-endemic countries and the prevention measures implemented so far by countries to contain the spread of the disease.